2000
DOI: 10.1146/annurev.matsci.30.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Copper Metallization for High Performance Silicon Technology

Abstract: ▪ Abstract  The increasingly rapid transition of the electronics industry to high-density, high-performance multifunctional microprocessor Si technology has precipitated migration to new materials alternatives that can satisfy stringent requirements. One of the recent innovations has been the substitution of copper for the standard aluminum-copper metal wiring in order to decrease resistance and tailor RC delay losses in the various hierarchies of the wiring network. This has been accomplished and the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
253
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(259 citation statements)
references
References 22 publications
2
253
0
1
Order By: Relevance
“…A similar thickness dependence of the selfannealing kinetics has been observed previously. 6,7,[24][25][26][27] Supported by the observation of even slower kinetics observed for Cu deposited in damascene trenches, 8,28,29 the thickness dependence has been attributed to geometrical constraints due to trench and via structures and/or the interface and surface of the film. 8 This, however, does not explain the complete absence of self-annealing in the thinnest Cu layer, as observed in the present study, since the as-deposited crystallite sizes are considerably smaller than the layer thickness.…”
Section: B Kinetics Of Self-annealingmentioning
confidence: 99%
“…A similar thickness dependence of the selfannealing kinetics has been observed previously. 6,7,[24][25][26][27] Supported by the observation of even slower kinetics observed for Cu deposited in damascene trenches, 8,28,29 the thickness dependence has been attributed to geometrical constraints due to trench and via structures and/or the interface and surface of the film. 8 This, however, does not explain the complete absence of self-annealing in the thinnest Cu layer, as observed in the present study, since the as-deposited crystallite sizes are considerably smaller than the layer thickness.…”
Section: B Kinetics Of Self-annealingmentioning
confidence: 99%
“…1 A process to deposit a uniform and continuous thin film ( < 2 nm) of copper in high aspect ratio structures is desirable in order to meet the demands of current trends in integrated circuit technology. Deposition techniques including physical vapour deposition (PVD), 2 electrodeposition, 3 chemical vapour deposition (CVD), 4 and atomic layer 1-17 | 1 deposition (ALD) 5 have been applied with the aim of obtaining such a thin film. However, it is extremely difficult to deposit thin films of Cu at this thickness and instead islands of Cu tend to be more favourable.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Unfortunately, the typical temperature requirement for these reactions (200-400°C) causes dewetting which leads to discontinuous copper films. Recently, Sung et al reported thermal ALD of copper metal using the reaction of copper dimethylamino-2-propoxide [Cu(dmap) 2 ] and diethylzinc [ZnEt 2 ] at 100-120°C. 5 However, subsequent work reported that the parasitic chemical vapour deposition reaction of ZnEt 2 may lead to Zn incorporation into the copper thin film.…”
Section: Introductionmentioning
confidence: 99%
“…After plating, the overburden above the trenches is also 111-textured, despite the random orientations found on the sidewall seed. 24 These differences have important implications for transformation kinetics, according to the recent work on electroplated films. Several such studies using high resolution x-ray diffraction found that films deposited on untextured seed layers recrystallized faster than their textured counterparts, but resulted in smaller final grain size and lower final 111 texture.…”
mentioning
confidence: 99%